The Role of Zakat Literacy and Service Quality on Muzakki Trust - Gading Muliati, Rahmayanti; Rahmawati; Junaidi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the level of financial literacy, especially zakat among Muzakki, as well as a summary of the level of Muzakki trust in the accountability of Zakat management institutions in Palopo City. Data was collected using a purposive sampling method with an online survey approach. 115 Muzakki participated in the research and Structural Equation Modeling (SEM) was used to analyze the data and test the hypothesis. This research found that financial literacy, especially regarding Zakat, has a positive and significant effect on the trust and accountability of Zakat Management Institutions. On the other hand, the service quality of Zakat Management Institutions does not have a positive effect on trust and accountability. Furthermore, the accountability of Zakat Fund managers influences Muzakki’s trust in Zakat Management Institutions. This proves that financial literacy increases people’s awareness of paying zakat.